Kangaroo mother care and outcome of neonates with low birth weight - Zahraa Adnan Hassan; Faris Mohammed Al-Haris; Alaa Jumaah Manji Nasrawi (Zdorovʹe Rebenka)
Background. Kangaroo mother care (KMC), a type of newborn care involving skin-to-skin contact with the mother or other caregiver, reduces mortality in infants with low birth weight (< 2.5 kg) when initiated after stabilization. In this study, we attempt to compare the outcomes of low-birth neonates admitted to a recently established KMC unit in Al-Zahraa Hospital to neonates discharged to homes without KMC training. Materials and methods. A case-control study was conducted in Al-Zahraa Teaching Hospital at Al-Najaf Al-Ashraf (Iraq) to evaluate the outcomes of neonates with low birth weight (< 2.5 kg) who were admitted to the kangaroo mother care unit (cases) in comparison to those neonates with comparable body weight who were discharged home without KMC training (controls). The primary outcome was the mortality rate. The secondary outcomes were duration of hospital stay, complications, and breastfeeding. Results. Neonates at the KMC unit were discharged at a mean of 7.3 days compared to 9.4 days at the neonatal intensive care unit (P = 0.041); they had lower incidence of hypothermia (P = 0.011), hypoglycemia (P < 0.0001), sepsis (P < 0.0001) and less readmission rate (P < 0.0001), lower mortality rate (P = 0.016) and earlier breastfeeding with better LATCH scores. Conclusions. The application of the KMC significantly reduced the duration of hospital stay, morbidities, and mortality rate and improved breastfeeding considerably compared to the regular neonatal intensive care unit in preterm low-birth-weight infants.